Microstructure With Scanning Electron Microscope And Sensory Characteristics In Nori Red Algae (Gracilaria Gigas) - Pinctada Putri Pamungkas; Asriati Djonu (AGRITEPA: Jurnal Ilmu dan Teknologi Pertanian, 2022)
Gracilaria is a red algae seaweed (Rhodopyceae) and can be developed by being cultivated in the sea, ponds and river estuaries. Red seaweed of the Gracilaria sp species is found and cultivated as a source of raw material for the production of food grade agar in Indonesia. Gracilaria gigas type seaweed has the potential as a raw material in the manufacture of nori products. Utilization of Indonesian local seaweed, will minimize imports of seaweed from various seaweed-producing countries. Gracilaria gigas red seaweed contains 5.84% water content, 0.44% fat content, 7.27% crude fiber, 23.76% protein, 11.92% ash, 180.52% carbohydrates and 19,922 IC50 antioxidants. mg AAE/g. Acceptance of Nori made from Gracilaria gigas seaweed using sensory analysis with the RATA (Rate All That Apply) method, sensory testing was carried out using 8 test parameter attributes, resulting for the parameters tested for salty taste of 2.05, seaweed taste of 1.50, aroma seaweed 1.35, crunchy texture 1.50, smooth texture 2.00, thick texture 1.35, green color 1.25 and elasticity 1.50. For microstructural analysis using a Scanning Electron Microscope with a magnification of 5000x.